Synopsis of the fossil flat wasps Epyrinae (Hymenoptera, Bethylidae), with description of three new genera and 10 new species. (5th February 2021) - Colombo, Wesley D.; Perkovsky, Evgeny E.; Waichert, Cecilia; Azevedo, Celso O.
Abstract : The subfamily Epyrinae is the most common in the bethylid fossil record. Its geological history ranges from the Eocene to the Pleistocene, and it is the only subfamily that has no records in the Cretaceous. Here we revise, diagnose and illustrate known epyrine fossil wasps. A new genus is proposed, † Gloxinius Colombo & Azevedo gen. nov., to contain the species † Gloxinius bifossatus (Brues, 1939 ) comb. nov., transferred from Epyris Westwood, 1832 . The species † Chlorepyris concaptus (Brues, 1933 ) comb. nov., † Chlorepyris invelatus (Brues, 1933 ) comb. nov. and † Chlorepyris setosus (Brues, 1933 ) comb. nov. are transferred from Epyris Westwood, 1832 to Chlorepyris Kieffer, 1913a . Three species are transferred from Epyris Westwood, 1832 to Pristocerinae: † Merascylla Colombo & Azevedo gen. nov. is proposed to contain † Merascylla atavella (Cockerell, 1920 ) comb. nov., and † Pseudisobrachium elatus (Brues, 1933 ) comb. nov. and † Pseudisobrachium inhabilis (Brues, 1923 ) comb. nov. are transferred to Pseudisobrachium Kieffer, 1904a . One species is transferred from Epyris Westwood, 1832 to Scleroderminae: † Mael Colombo & Azevedo gen. nov. is proposed to contain † Mael longiceps (Brues, 1923 ) comb. nov. Ten new species are described from Baltic and Rovno ambers: † Chlorepyris deploegi Colombo & Azevedo sp. nov., † Chlorepyris engeli Colombo & Azevedo sp. nov., † Chlorepyris hopei Colombo & Azevedo sp. nov., † Chlorepyris jouaulti Colombo & Azevedo sp. nov., † Chlorepyris mckellari Colombo & Azevedo sp. nov., † Chlorepyris meunieri Colombo & Azevedo sp. nov., † Chlorepyris neli Colombo & Azevedo sp. nov., † Chlorepyris perrichoti Colombo & Azevedo sp. nov., † Holepyris rasnitsyni Colombo & Azevedo sp. nov. and † Holepyris terayamai Colombo & Azevedo sp. nov. The species † Laelius nudipennis Brues, 1933 is no longer classified as Bethylidae and it is transferred to Platygastroidea incertae sedis . Eighty-one fossil species are now recognized in Bethylidae, with 30 belonging to Epyrinae and distributed within six genera. A key for fossil epyrines is provided. http://zoobank.org/urn:lsid:zoobank:org:pub:A7481392-3BD2-45F3-A035-34E515A34218